If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 2) = -35 Reorder the terms: -5(2 + x) = -35 (2 * -5 + x * -5) = -35 (-10 + -5x) = -35 Solving -10 + -5x = -35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -5x = -35 + 10 Combine like terms: -10 + 10 = 0 0 + -5x = -35 + 10 -5x = -35 + 10 Combine like terms: -35 + 10 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| 15a^3b^2-45a^2b^3-60a^2b=0 | | 24z+35z^2-35= | | 7c+7=567 | | 6(2-3q)-5(8q+3)= | | -5a+7=-23 | | 5x+3=3x+27 | | 7x^2+45x-28=0 | | 5m-7=5(m-2)+3 | | -3(3h-1)=-7h-5 | | -3.2y+8.3y=-15.3 | | 29=15x-(4+4x) | | 4x^2+6x+15=0 | | (1+-3(.75+-.625z)-z)+4(.75+-.625z)-z=2 | | 2x+4=3x-24 | | 9r+18=882 | | 2x^2+4x+2= | | 12720-20x=0 | | 12720-20x= | | 2(x-5)+7=23 | | 2x-5=7x-9 | | (1+-3y-z)+4(.75+-.625z)-z=2 | | 11x^2-21x-2= | | 2m-9=2(m-8)+7 | | 4x+5=401 | | -14x^2+x^4+49=0 | | 12720-20*3.75= | | 22y^2-31y+9= | | 0.125x=0.5 | | 4j+20=388 | | 3x+2=-23 | | 4(m-2)=4m | | 12720-(20*3.75)= |